Internal Control, Internal Auditing, and Operations Auditing for Hospitals (Book). - Burns, Thomas J.; Dickens, Robert L. (The Accounting Review, 1980)
Reviews the book "Internal Control, Internal Auditing, and Operations Auditing for Hospitals."